“This is my why.” Exploring the concept of meaningful work in early-career veterinarians across Canada - Morabito, Emily; Jones, Andria; Kittisiam, Tipsarp; Cake, Martin; Ritter, Caroline (Frontiers in Veterinary Science, 2025)
IntroductionThe veterinary profession is marked by significant mental health challenges, including stress and burnout, particularly among early-career veterinarians. Positive psychology highlights the importance of meaningful work as a pathway to enhance well-being (e.g., increasing resilience through a sense of purpose). Despite this, there is limited understanding of how early-career veterinarians perceive and experience meaningful work during the transition from student to practitioner.MethodsThis study aimed to: (1) explore early-career veterinarians’ perceptions of meaningful work, and (2) investigate the intricacies of meaningful work experienced by early-career veterinarians during the transition period. A qualitative, phenomenological approach was utilized, involving semi-structured interviews with 21 early-career veterinarians from Canadian veterinary colleges. Data were analyzed using template analysis to identify themes in the data.ResultsThe analysis identified five key themes: the obscure concept of meaningful work, meaning found through connection, making a difference, the ability to be creative and problem-solve, and the evolving nature of meaning. Participants initially found meaningful work difficult to define, reflecting its subjective nature. Connections with animals and humans, such as clients and colleagues, emerged as crucial sources of meaning. Making tangible differences for animals, caretakers, and the community was seen as central to their work. The ability to creatively solve problems provided intellectual satisfaction and enhanced their sense of purpose. Participants noted that their understanding of meaningful work evolved with experience, highlighting the interplay between professional growth and personal fulfillment.DiscussionIn conclusion, early-career veterinarians derived meaningful work from a combination of deep connections, impactful contributions, and creative problem-solving, which evolved over time. These insights can inform strategies to improve well-being within the profession by fostering supportive environments that encourage reflective practices, personal growth, and pathways to meaning and purpose.